Re-engineering change in higher education - David Allen; N. Fifield (Information Research: An International Electronic Journal)
Business Process Re-engineering (BPR) is being used in a number of UK Higher Education Institutions (HEIs) as a change management strategy. Whilst the focus of these HEIs is on re-engineering administrative services, there are also tentative attempts to redesign teaching and learning. This paper adopts a case study approach to determine the applicability of BPR to HEIs. The research started from a broad research question: How does organisational culture in HEIs impact on the implementation of BPR programmes? The conclusions drawn from the research are that the organisational culture and structure of HEIs limit the degree of change sought from a BPR project: the focus of the case study HEIs was on incremental process improvement of administrative services. The projects in these institutions were not about radical change. BPR techniques are shown to have something to offer HEIs in terms of co-ordinating administrative activities, but the emphasis on IT and processes in project design means the human resources change necessary for significant gains in efficiency is unlikely.